A influência da estrutura de propriedade e controle sobre a estrutura de capital : um estudo empírico no mercado acionário brasileiro de 2010 a 2016 - Jardim, José Renato de Paula Souza (2018)
One of the main financial policies is related to the capital structure that companies define for themselves. Due to this reason, determinants of factors of capital structure is a high priority topic on the agenda of financial researchers. However, the main objective of this research is to determine if the capital structure of Brazilian public companies is influenced by their own ownership structure and by it‟s capital concentration. We utilize the major last shareholder (MAU1) and the three major last shareholders (MAU3) and their characteristics, be them a family company, foreign capital, government, BNDES or pension fund. Cut-offs between 10% to 50% are utilized based on the corporate finance theory. The sample studied comprises 128 Brazilian companies listed on the B3 stock exchange. The data comprises the period between 2010 and 2016, excluding financial companies from the sample. To verify the influence of capital structure fixed effects panel data with robust regressions are used. The results corroborate that which is expected by the theory. However, excess capital concentration hurts debt financing. Another important characteristic of the Brazilian stock market is the prevalence of companies with founding families as controlling members, this leads to a reduced use of debt financing due to worries related to loss of control. In the other hand the existence of foreign capital, government, BNDES and pension funds has a positive relationship with debt financing. We point to the effect of ownership structure on the capital structure of companies, the utilized methodology regarding reference forms which allows us to detect the last major shareholder in detail, and the more complex ownership structure (pyramidal) for companies as possible original and relevant contributions to the literature that result from this research. We also analyze the comprehensiveness and contemporaneous quality of the sample: The data used starts at the creation of the reference forms in January of 2010 until the end of2016 – published in December 2017 – and finally, the new explanatory variables in capital structure literature (capital concentration and nature of the ownership structure).